The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1074/jbc.m309349200
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle-dependent Phosphorylation of the Large Subunit of Replication Factor C (RF-C) Leads to Its Dissociation from the RF-C Complex

Abstract: The five subunit replication factor C (RF-C) complex plays a critical role in DNA elongation. We find that the large subunit of RF-C (RF-Cp145) is phosphorylated in vivo whereas the smaller RF-C subunits are not phosphorylated. The phosphorylation of endogenous RFCp145 is modulated in a cell cycle-dependent manner. Phosphorylation is maximal in G 2 /M and is inhibited by an inhibitor of cyclin-dependent kinases. Phosphorylation of purified recombinant RF-C complex in vitro reveals that RF-Cp145 is preferential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…Coimmunoprecipitation experiments using antibodies against RFC140 (for the RFC1-5 complex) and RFC37 (for the RFC2-5 complex), respectively, were performed. As previously demonstrated, 17 RFC140 coimmunoprecipitated with RFC40 (Fig. 5A, left panel) but not with RIα (Fig.…”
Section: Resultssupporting
confidence: 81%
“…Coimmunoprecipitation experiments using antibodies against RFC140 (for the RFC1-5 complex) and RFC37 (for the RFC2-5 complex), respectively, were performed. As previously demonstrated, 17 RFC140 coimmunoprecipitated with RFC40 (Fig. 5A, left panel) but not with RIα (Fig.…”
Section: Resultssupporting
confidence: 81%
“…A study has indicated that RFC catalyzed the formation of a cyclic structure of PCNA around the primers in an ATP-dependent manner ( 35 ). Munshi et al ( 36 ) observed that cyclin-dependent kinases reduced the stability of RFC, inactivating it in the S phase to regulate DNA replication ( 36 ). However despite being an important component of the RFC, the role of RFC5 in lung cancer remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…40 Several major replication proteins such as DNA polymerase alpha, replication factor C, and Fen 1 are phosphorylated by CDK/ cyclins both in vitro and in vivo. [41][42][43][44][45] Our earlier work showed that pol δ catalytic subunit, p125, 32 is a potential substrate of CDKs/ cyclins in vivo. The small subunit, p50 (Fig.…”
Section: Discussionmentioning
confidence: 99%